(untitled) (Research, Society and Development, 2024)
Goal. To analyze, through a systematic review, the prevalence of access to dental services in Brazilian Basic Health Units. Methods: A systematic review and meta-analysis were carried out. Studies published between January 2002 and September 2023 were selected in the databases Latin American and Caribbean Literature in Health Sciences (LILACS), MEDLINE (via PubMed), Scientific Electronic Library Online (SciELO) and Scopus. The search strategy was prevalence AND access to health services AND oral health services AND Brazil. (DeCS and Words) or prevalence AND health services accessibility AND dental health services AND brazil. The primary outcome was the prevalence of access to Oral Health services in PHC with its respective 95% Confidence Interval. The chi-square test (χ2) was used, with a significance of (p < 0.10) to assess heterogeneity. Results. The pooled prevalence of access to oral health services among individuals investigated was 34% (95%CI: 0.17 - 0.51). The heterogeneity between studies was substantial, demonstrated by the Q test (p < 0.001) and the I2 statistic (I2 = 99.94%). Conclusion: The present study demonstrates a 34% prevalence of access to dental services and factors such as income, diet, education level and service availability are strongly linked to obtaining dental treatments, having a direct impact on people’s quality of life.